Greenland Ice Sheet Elevation Change: Direct Observation of Process and Attribution at Summit. Issue 22 (11th November 2020) - Hawley, Robert L.; Neumann, Thomas A.; Stevens, C. Max; Brunt, Kelly M.; Sutterley, Tyler C.
Abstract: Greenland Ice Sheet surface elevation is changing as mass loss accelerates. In understanding elevation change, the magnitudes of physical processes involved are important for interpretation of altimetry and assessing changes in these processes. The four key processes are surface mass balance (SMB), firn densification, ice dynamics, and isostatic adjustment. We quantified these processes at Summit, Greenland, where monthly Global Navigation Satellite System (GNSS) snowmobile traverses measured elevation change from 2008 to 2018. We find an elevation increase of 0.019 m a −1 . The sum of the effects of the four processes reproduces the measured elevation time series, in linear trend and in intra‐annual variability. The short‐term variability in elevation is primarily explained by the variability in SMB. Since SMB has not changed significantly over the last century, and the other processes change over longer time scales, the elevation change likely has been ongoing for at least the last 100 years. Key Points: Measurements of ice sheet elevation, flow divergence, firn densification, and accumulation are self‐consistent at Summit, Greenland The ice sheet surface at Summit, Greenland, is rising at 1.9 cm/year over the last decade, a trend likely unchanged in the last century Short‐term ice sheet elevation changes are dominated by surface mass balance changes